2009
DOI: 10.1002/cjoc.200990246
|View full text |Cite
|
Sign up to set email alerts
|

Electrosyntheses of α ‐Hydroxycarboxylic Acids from Carbon Dioxide and Aromatic Ketones Using Nickel as the Cathode

Abstract: With Ni as the cathode and Al as the anode, aromatic ketones (acetophenone, benzophenone, 6-methoxy-2-acetonaphthone, 4-methylacetophenone and 4-methoxyacetophenone) could be successfully electrocarboxylated with CO 2 (4 MPa) in an undivided cell containing n-Bu 4 NBr-DMF electrolyte at a constant current under room temperature, affording the corresponding α-hydroxycarboxylic acids in good to excellent yields (56%-90%). The experimental results showed that the yields of the target products were strongly depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
0
24
1
Order By: Relevance
“…A recent report by Yuan and co-workers detailed a protocol for the reductive carboxylation of ketones (Figure 46F, top). 808 Although the scope of substrates is limited to aromatic ketones, α -hydroxycarboxylic acids were generally obtained in good yields together with small amounts of pinacol byproducts. Since the reduction potentials of ketones are close to that of CO 2 , it is proposed that the reduction of both CO 2 and ketones could occur under galvanostatic conditions.…”
Section: Cathodic Reductionmentioning
confidence: 99%
“…A recent report by Yuan and co-workers detailed a protocol for the reductive carboxylation of ketones (Figure 46F, top). 808 Although the scope of substrates is limited to aromatic ketones, α -hydroxycarboxylic acids were generally obtained in good yields together with small amounts of pinacol byproducts. Since the reduction potentials of ketones are close to that of CO 2 , it is proposed that the reduction of both CO 2 and ketones could occur under galvanostatic conditions.…”
Section: Cathodic Reductionmentioning
confidence: 99%
“…This offers an electrochemical route for several commercially relevant α-aryl propionic acids, used as non-steroidal anti-inflammatory drugs (NSAIDs) [80]. Therefore, the electrocarboxylation of aromatic ketones with sacrificial anodes has been extensively investigated [7577 8198]. Some researchers focused on replacing toxic and volatile organic solvents with ionic liquids [8183].…”
Section: Reviewmentioning
confidence: 99%
“…The cathode material again plays an important role in the electrocarboxylation of carbonyl compounds. Toxic lead cathodes [85] and expensive platinum cathodes [87] can easily be replaced by better performing stainless steel [90] and nickel [75,89]. Concerning the reactivity of carbonyl compounds, it has been demonstrated that the carboxylation rate of benzophenones is decreased by electron donating substituents [90].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations